GERMAN DEBT ISSUES: 1970-1993 - Consiglio, John A. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Management of its national debt was Germany’s main foscal policy problem during the period over 1970 to 1993. The reunification solidarity pact, which involved plans to step up new borrowing, drew Bundesbank warnings, and many sides demanded consolidation measures in the forms of spending cuts and tax increases. While many justifiably consider stark size, and strong inherent fundamentals, as main reasons for German economic might, others look at that country’s stances in the face of specific economic issues as a reason for the country’s ability to retain its European economic primacy. In this paper we look at how Germany has viewed, and acted upon, the issue of national debt and this debt’s size and growth, as in fact a national fiscal-policy problem.